2014
DOI: 10.1111/are.12467
|View full text |Cite
|
Sign up to set email alerts
|

Grow-out culture of abaloneHaliotis tuberculata coccineaReeve, fed land-based IMTA produced macroalgae, in a combined fish/abalone offshore mariculture system: effect of stocking density

Abstract: Haliotis tuberculata coccinea has been identified as a target species for European aquaculture development, in order to fulfil the rising demand for abalone. The effects of different stocking densities on the growth performance, feed utilization and survival of two different initial size groups (30 and 40 mm) of abalones, during the final grow‐out to cocktail/market size (45–60 mm), were determined over a 6‐month period. Trials were performed in abalone cages installed in a commercial open‐sea cages fish farm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 51 publications
1
7
0
2
Order By: Relevance
“…There was a clear trend of negative correlation between stocking density and body weight growth rate. This negative effect is consistent with many studies in aquatic animals (Dunham, Gurney-Smith, Plamondon, Yuan, & Pearce, 2013;Irwin et al, 1999;Lund, Steenfeldt, Herrmann, & Pedersen, 2013;Mgaya & Mercer, 1995;Pei, Dong, Wang, Tian, & Gao, 2012;Sookying, Silva, Davis, & Hanson, 2011;Viera, Gercende, Fernández Palacios, & Izquierdo, 2016), including sea urchins (Qi et al, 2016;Siikavuopio et al, 2007;Siikavuopio & James, 2011). Christiansen and Siikavuopio (2007) also reported that the growth rate of the sea urchin S. droebachiensis stocked at low density was not significantly affected by the stocking density.…”
Section: Stocking Density Effectsupporting
confidence: 89%
“…There was a clear trend of negative correlation between stocking density and body weight growth rate. This negative effect is consistent with many studies in aquatic animals (Dunham, Gurney-Smith, Plamondon, Yuan, & Pearce, 2013;Irwin et al, 1999;Lund, Steenfeldt, Herrmann, & Pedersen, 2013;Mgaya & Mercer, 1995;Pei, Dong, Wang, Tian, & Gao, 2012;Sookying, Silva, Davis, & Hanson, 2011;Viera, Gercende, Fernández Palacios, & Izquierdo, 2016), including sea urchins (Qi et al, 2016;Siikavuopio et al, 2007;Siikavuopio & James, 2011). Christiansen and Siikavuopio (2007) also reported that the growth rate of the sea urchin S. droebachiensis stocked at low density was not significantly affected by the stocking density.…”
Section: Stocking Density Effectsupporting
confidence: 89%
“…그러나 기존 연구는 치패와 중간육성 크기를 중심으 로 한 수용밀도 연구로 한정되어 있으며, 특히 해상가두리에서 는 북방전복이 최대 2년산까지의 적정 수용밀도만 보고되어 있어 (Yoon et al, 2004;Kim et al, 2014) Kim et al (1998; et al, 1988;Mgaya and Mercer, 1995;Capinpin et al, 1999;Yoon et al, 2003;Viera et al, 2014;Kim et al, 2013;. (Koike et al, 1979;Peck, 1983;Hadley and Manzi, 1984;Allan and Maguire, 1992;Parsons and Dadswell, 1992;Holliday et al, 1993;Mgaya and Mercer, 1995), 石田 ( and Mercer, 1995;Nie et al, 1996;Capinpin et al, 1999;Jarayabhand et al, 2010;Viera et al, 2014 …”
Section: 국내에 수용밀도에 따른 전복류 양성에 관한 연구로는 1년unclassified
“…It is wellknown for forming free-floating "green tides" such as the blooms of U. prolifera that appear annually in the Yellow Sea and disrupted the 2008 Beijing Olympics sailing events (Li et al, 2016). Ulva provides services for the food industry (Rouxel et al, 2001) and is used in aquaculture of fish (Azaza et al, 2008) and marine invertebrates such as shrimps and abalone (Cruz-Suarez et al, 2010;Brito et al, 2013;Viera et al, 2016). Due to their high photosynthetic and growth rates (Longstaff et al, 2002;Figueroa et al, 2009), Ulva species are used as biofilters in integrated multi-trophic aquaculture systems to reduce organic loads from fish effluents (Bartoli et al, 2005;Korzen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%